Management of Full-Thickness Lower Eyelid Defect After MOHS Procedure and Mustard Flap: Poster Presentation - Case Report - Ophthalmologist - SRI IRMANDHA KUSUMAWADHANI; HISAR DANIEL; YUNIA IRAWATI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Large full-thickness eyelid defects are considered a challenging case. This study reports how to manage the reconstruction of eyelid defect in a case with a history of carcinoma cell basal of the eyelid, which is removed with MOHS procedure and mustard flap reconstruction but full-thickness of more than 50% defect of the lower eyelid remains. Case Illustration : A 67 years old woman was referred from the dermatology and venereology clinic with a history of eyelid cancer operation, 13 days prior. The patient's chief complaint was the left lower eyelid felt pulled down. Examination revealed a left lower eyelid full-thickness defect of more than 50% and ectropion at the lateral side. An 8 mm lagophthalmos without corneal exposure was present. The reconstruction was done with a lips mucosa graft to form posterior lamella, at the medial side anterior lamella was formed by the glabellar flap, and at the lateral side was formed by a skin graft due to lack of the anterior lamella from the mustard flap previously. Discussion : Eyelid reconstruction aims to provide adequate globe protection. The principle management of reconstruction in full-thickness eyelid defects horizontally of more than 50% can’t be done by an anterior flap (mustard) only because it's unstable and the eyelid can be retracted. The reconstruction must consist of the anterior and posterior lamella which have to be tight to the periosteum. Conclusion : One step procedure for large defects of the lower eyelid after cancer removal can be done with considering the proper plan of reconstruction technique.